Development of a financial software for the simulation of investment portfolios in the colombian capital market [Desarrollo de un software financiero para la simulación de portafolios de inversión en el mercado de capitales colombiano] (2020)
In the context of Revolution 4.0 influenced by the digitalization of most economic and social production processes, education cannot be kept out of the way; In this line, financial knowledge is an area that businessmen, investors and financial entities demand, since adequate knowledge about financial products enables an analysis of risk exposure and decision-making that promotes the growth of the economy. This work presents the development of a software for the simulation of investment portfolios in the Colombian Capital Market based on gamification techniques, this development includes 5 stages: user contact with the video game, access to financial information, selection of financial assets (variables), results and decision making. © 2020, Associacao Iberica de Sistemas e Tecnologias de Informacao. All rights reserved.